The implementation of integrated marketing communication strategies to enhance the appeal of ngargoretno tourism village in the digital era - Pinontonan, Nexen Alexandre (International Journal on Social Science, Economics and Art, 2024)
This study aims to explore the implementation of integrated marketing communication strategies in enhancing the appeal of Ngargoretno Tourism Village in the digital era. With its significant potential as a prominent tourism destination, the management of Ngargoretno Tourism Village requires a holistic and synergistic marketing approach to strengthen its competitiveness in an increasingly digitized tourism market. The research questions addressed in this study include: (1) what forms of integrated marketing communication are employed by the management of Ngargoretno Tourism Village, and (2) what challenges and obstacles are encountered in the implementation of these strategies. Utilizing a qualitative approach with interactive model analysis, this research collects data through in-depth interviews and field observations with key stakeholders. The study aims to provide strategic insights into the role of integrated marketing communication in reinforcing the positioning of Ngargoretno Tourism Village in the digital era, while also identifying operational barriers that must be addressed to ensure the sustainability of digital-based tourism growth.